Laundry detergent compatibility of the alkaline protease from Bacillus cereus - Banik, R.M.; Prakash, M. (Elsevier GmbH, 2004)
The endogenous protease activity in various commercially available laundry detergents of international companies was studied. The maximum protease activity was found at 50°C in pH range 10.5-11.0 in all the tested laundry detergents. The endogenous protease activity in the tested detergents retained up to 70% on incubation at 40°C for 1h, whereas less than 30% activity was only found on incubation at 50°C for 1h. The alkaline protease from an alkalophilic strain of Bacillus cereus was studied for its compatibility in commercial detergents. The cell free fermented broth from shake flask culture of the organism showed maximum activity at pH 10.5 and 50°C. The protease from B. cereus showed much higher residual activity (more than 80%) on incubation with laundry detergents at 50°C for 1h or longer. The protease enzyme from B. cereus was found to be superior over the endogenous proteases present in the tested commercial laundry detergents in comparison to the enzyme stability during the washing at higher temperature, e.g., 40-50°C.
Keywords: Alkaline protease; Bacillus cereus; Detergent compatibility; Laundry detergents; Thermostability